Modeling the geographic spread and proliferation of invasive alien plants (IAPs) into new ecosystems using multi-source data and multiple predictive models in the Heuningnes catchment, South Africa - Bhongolethu Mtengwana; imothy Dube; Bester Tawona Mudereri; Cletah Shoko (Taylor and Francis Online, 2023)
Abstract